Pengaruh Kompetensi dan Penempatan Kerja terhadap Motivasi Prajurit Serta Dampaknya Pada Kinerja Prajurit Kodim 0726 Sukoharjo - Slamet Riyadi; Iwan Kurniawan Subagja; Hary Indratjahyo (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2025)
This study aims to determine influence of competence and job placemente on soldier motivation and its impact on soldier performance Kodim 0726 Sukoharjo. The study was conducted on soldiers of Kodim 0726 Sukoharjo with a sampling technique using saturated sampling technique. The data analysis method used descriptive analysis and path analysis. The results of the study showed that: 1) There is an influence of competence on soldier performance; 2) There is an influence of job placement on soldier performance; 3) There is an influence of competence on soldier motivation; 4) There is an influence of job placement on soldier motivation; 5) There is an influence of soldier motivation on soldier performance; 6) There is no influence of competence on soldier performance through soldier motivation; and 7) There is no influence of job placement on soldier performance through soldier motivation.